From Bureaucracy to Expertise: Empowering Knowledge Workers in Public Service (The Case of the Directorate General of Customs and Excise) - Setiawan, Hendra Bagus; Rosari, Reni (Puslatbang KDOD Lembaga Administrasi Negara, 2025)
The Directorate General of Customs and Excise (DGCE) is undergoing a transformative process aligned with bureaucratic reform objectives to achieve worldclass status. This transition involves a shift from structural to functional roles, focusing on prioritizing expertise and skills. In this evolving environment, functional officers are increasingly recognized as akin to knowledge workers, highlighting the need for strategic HR approaches to maximize their knowledge as a core asset. This study examines the impact of approaches that enhance knowledge worker productivity (KWP) on functional officers by promoting personal knowledge management (PKM) through idiosyncratic job design reflected in dimensions, such as job definition, job autonomy, innovation as a job requirement, and lifelong learning orientation. Data was gathered from 249 functional officers at the DGCE through Google Forms. The Structural Equation Modeling method, employing a Partial Least Square, was utilized for data analysis. The findings reveal several vital insights: job definition and lifelong learning orientation emerge as significant positive drivers of PKM. While job autonomy exhibits a positive effect, it is notstatistically significant. Interestingly, innovation as a job requirement demonstrates a non-significant negative impact. Moreover, the study underscores the significant and positive influence of PKM on KWP. Based on these findings, the study recommends an organizational redefinition of functional officer productivity, providing organizational support to foster an environment conducive to PKM. Additionally, it recommends clarifying the scope of functional officer responsibilities and authorities, alongside optimizing the role of direct supervisors asfacilitators, bridging the gap between the organization and functional officers